ANALISIS PERSEPSI TAMU TERHADAP FASILITAS HOTEL NOVOTEL MANADO BERBASIS OTA (ONLINE TRAVEL AGENT) - Manadake, Florensia Grifit Junior; Lagarense, Bet El SIlisna; Sinolungan, Linda (HOSPITALITI DAN PARIWISATA, 2026)
This study aims to analyze guest perceptions of the facilities at Hotel Novotel Manado based on reviews posted on various online travel agent (ota) platforms such as traveloka, agoda, booking.com, tripadvisor, accor hotels, kayak, and skyscanner. in today’s digital era, customer reviews on online platforms have become a key indicator reflecting the quality of hotel services and facilities from the consumer’s perspective. This research employs a descriptive qualitative approach using content analysis on 50 purposively selected guest reviews. the reviews were analyzed and categorized into five main themes: room & cleanliness, restaurant & breakfast, swimming pool & gym, staff service, and additional facilities. The findings reveal that room conditions and cleanliness are the primary focus of guest perceptions, followed by staff service and breakfast quality. most reviews express positive sentiments, particularly regarding room comfort and staff friendliness, although some criticisms were noted concerning cleanliness, food variety, and additional facility quality. these insights serve as valuable input for the hotel to enhance service quality amid growing digital competition.